The Effect of Green Investment and Corporate Social Responsibility (Csr) on Financial Performance With Environmental Performance as a Moderating Variable in Energy Sector Companies on the Idx - Putri Panangguhan; Maiyaliza; Agustina (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to analyze the influence of Green Investment and Corporate Social Responsibility (CSR) on financial performance measured using Return on Assets (ROA) with Environmental Performance as a moderating variable in energy sector companies listed on the Stock Exchange. Indonesia (BEI) period 2021–2024. Study This use This study uses a quantitative approach with secondary data obtained from annual reports, sustainability reports, and the PROPER rating issued by the Ministry of Environment and Forestry. The research sample consisted of 10 energy sector companies with a total of 40 observations. The analytical method used is panel data regression with the Fixed Effect Model (FEM) and Moderated Regression Analysis (MRA) using EViews software. The results of the study show that Green Investment does not have a significant effect on ROA, indicating that green investment has not been able to provide a direct impact on the company's financial performance in the short term. Meanwhile, Corporate Social Responsibility (CSR) has a positive and significant effect on ROA, indicating that CSR disclosure can improve the financial performance of energy sector companies. Furthermore, Environmental Performance is unable to moderate the effect of Green Investment on ROA, but it is able to moderate and strengthen the effect of CSR on ROA. These findings indicate that the effectiveness of CSR in improving financial performance will be stronger if supported by by performance environment company Which Good. Study This provide implications that strategy sustainability company sector energy need emphasizes the quality of CSR implementation and environmental performance as important factors in improving financial performance.